Factors Influencing on Students’ Speaking Activities at University of Pasir Pengaraian - Rahayu, Pipit; Eripuddin; Mailinda, Elsa Talita; Antoni, Rivi (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
The purpose of this study was to determine the factors that influence students’ speaking activity. Speaking meant the ability to convey students’ thoughts. The problems of this research were students felt nervous because the students first, cannot speak in front of the audiences, second, students lack of vocabulary and they were not good in pronunciation and grammar.This research used descriptive qualitative research method. Data were taken from questionnaires and interviews. The population of this study was taken from fourth semester students, English Department, Pasir Pengaraian University. This class consists of 29 students. Research finding, There are two students strongly agree and sixteen students agree with the statement. Thus, the factor that greatly affects the speaking of fourth semester students was their concern about mistakes when they made speeches in front of the class.Based on the data, it could concluded that the factors that affect the speaking activity of fourth semester students of English Department at Pasir Pengaraian University was students who are worried about making mistakes when taking in front of the class.